Marketing Digital Interaktif : Analisis Strategi Tren Konten yang Membentuk Loyalitas Konsumen - Zuhrinal Nawawi; Luthfia Masfa Nur (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study uses a qualitative method to analyze content trend strategies in interactive digital marketing that contribute to building consumer loyalty. In today’s highly competitive digital era, companies are required to create strong engagement with consumers through digital platforms such as social media, websites, and applications. Content trends like storytelling, user-generated content, live streaming, and influencer usage have proven to attract audiences and encourage ongoing interaction. This research explores how these trends are applied by various brands and how consumers respond to these approaches over the long term. The findings show that message consistency, emotional value in content, and interactivity are key factors in forming emotional bonds that impact loyalty. Furthermore, two-way engagement between consumers and brands through comments, likes, and sharing features strengthens this relationship. By understanding consumer digital preferences and behaviors, content strategies can be dynamically adapted to maintain loyalty while expanding the relevant market reach.